Geometric and Electronic Structures of Nickel(II) Complexes of Redox Noninnocent Tetradentate Phenylenediamine Ligands - Ciccione, Jérémie; Leconte, Nicolas; Luneau, Dominique; Philouze, Christian; Thomas, Fabrice (Inorganic chemistry, 2016)
Five tetradentate ligands based on the N,N'-bis(2-amino-3,5-di-tert-butylphenyl)-o-phenylenediamine backbone were prepared, with different substituents at positions 4 and 5 (CH3 (3a), p-CH3O-C6H4 (3b), H (3c), Cl (3d), F (3e)). Their reaction with a nickel(II) salt in air affords the neutral species 4(a-e), which were isolated as single crystals. 4(a-e) feature two antiferromagnetically exchange-coupled diiminosemiquinonate moieties, both located on peripheral rings, and a diamidobenzene bridging unit. Oxidation of 4(a-e) with 1 equiv of AgSbF6 yields the cations 4(a-e)(+), which harbor a single diiminosemiquinonate radical. Significant structural differences were observed within the series. 4b(+) is mononuclear and contains a localized diiminosemiquinonate moiety. In contrast, 4c(+) is a dimer wherein the diiminosemiquinonate radical is rather delocalized over both peripheral rings. 4d(+) represents an intermediate case where the complex is mononuclear, but the radical is fully delocalized. Oxidation of 4(a-e) with 2 equiv of AgSbF6 produces the corresponding mononuclear dications. X-ray diffraction data on 4(b-d)(2+) reveals that the bridging ring retains its diamidobenzene character, whereas both peripheral rings have been oxidized into diiminobenzoquinone moieties. All the complexes were characterized by electrochemistry, EPR, and UV-vis-NIR spectroscopy. Remarkably, the electronic structures of the complexes differ from those reported by Wieghardt et al. for copper and zinc complexes of a related ligand involving a mixed N2O2 donor set (J. Am. Chem. Soc. 1999, 121, 9599). The easier oxidation of phenylenediamine moieties in comparison to aminophenols is proposed to account for the difference.